Eficiência e consistência de grupos indicadores para a representação de diferentes aspectos da diversidade de vertebrados - TRINDADE FILHO, Joaquim (2011)
Here we report the performance and consistency of indicator groups to inform conservationists about possible conservation planning scenarios in the Brazilian Cerrado and the Atlantic Forest. We explore the performance and consistency (group with equal efficiency and greater than chance in both biomes) of indicator groups for 1) determining which species are excluded when certain indicator groups are used; 2) determining the consistency of indicator groups in two Biodiversity Hotspots; 3) determining the performance of indicator groups to represent the functional diversity and unique bird species in the Atlantic Forest. To do so we used all the species of birds and mammals that occur in the Cerrado and Atlantic Forest. The performance of the indicator groups was evaluated by determining the percentage of all species captured in by candidate taxa against a null model (randomly assorted species sets) and against an "ideal model" (which included all species). We showed that good indicator groups require a relatively small covered areas (less than 2% of the studied biomes) to represent all species and ensure long-term persistence. Our study also emphasize restricted-range species as the only group capable of representing all species in an effective and consistent way. We also showed that it is possible to account for ca. 84.93% and 90.76% of all bird functional diversity and ca. 87.28% and 73.68% of all species originality of the Atlantic Forest in less than 0.64% of the biome total area. We highlight that restricted-range species are the best indicator group to represent the functional diversity. This group is of particular importance for conservation, since only with its use we can protect groups of species of ecological importance, e.g. endemic and endangered species, and guarantee the conservation of ecosystem processes, as well as the persistence and resilience of these imperiled ecosystems.